(untitled) - Nkomo, Stella M.; Stella M. Nkomo; Myron D. Fottler; R. Bruce McAfee (Mason, OH)
A fresh emphasis on problem solving and critical analysis equips you with long-term skills that are important for success at any level of study. Timely examples are drawn from a variety of organizations, including today's growing service sector to provide you with a diversity of experience. The book's timely topics prepare you for traditional HRM situations as well as today's more controversial issues, such as telecommuting, alcohol and drug abuse on the job, and discrimination. With exercises designed for a single class period and a new comprehensive term project, you'll find opportunities to apply and refine your HRM skills for success within your introductory course and your career that follows
Keywords: Personnel management; Personnel management